DhÃ¢t dan Sifah Tuhan dalam Konsep Tauhid Muâtazilah - Zarkasyi, Amal Fathullah (ISLAMICA: Jurnal Studi Keislaman, 2010)
In Islamic thought, Muâtazilah has been classified as a rational form of current of thought. This paper is interested in exploring in a deeper manner this Mutazilite rationalism be referring specirfically to its concept of tauhid. We argue that Muâtazilah is concerned simply with presenting this concept in its purest form. Hence, they reject the notion of God having similarity with His creatures (tashbÃ®h) and of Him having earthly body (tajsÃ®m). Interestingly however, the Muktzilah is not always consistent with this general hypothesis, and argue for example that the attributes of Godâlike His words, the Qurâanâare created (makhlÃ»q). We will try to expose that inconsistence as part of our critique to the Muâtazilah. The paper will also discuss proportionately the problems of tawh Ã®d rubÃ»bÃ®yah and tauhid al-dhÃ¢t wa al-s ifah, of which the Muâtazilah has given reasonably especial attention. With regard to tauhid ulÃ»hÃ®yah, the paper will only speak in general terms considering that the concept has not recived a clear explanation of the Muâtazilah. We understand nonetheless that this latter concept is about a rasional argumentation concerning the existence of God.